The Mediating Role of Satisfaction in the Relationship Between Brand Image, Price, Service Quality, and Digital Marketing on Student Loyalty in Higher Education - Biliam Abiyut Nomleni; Ronny H. Walean; Deske W. Mandagi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
In the increasingly competitive higher education sector, understanding the determinants of student satisfaction and loyalty is essential for institutional sustainability. This study aims to examine the influence of brand image, price, service quality, and digital marketing on student satisfaction and loyalty in a higher education context. The research was conducted at Universitas Klabat with a sample of 370 students selected through a purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that brand image, price, and service quality have positive and significant effects on student satisfaction, whereas digital marketing does not. Moreover, brand image, price, service quality, and satisfaction do not exert a significant direct impact on student loyalty. Instead, digital marketing demonstrates a positive and significant direct effect on student loyalty. These results highlight the importance of managing brand perception, pricing strategies, and service quality to enhance student satisfaction, while also emphasizing the crucial role of digital marketing in strengthening student loyalty. Additionally, the study reveals that student satisfaction does not serve as a significant mediator in the relationship between the independent variables and student loyalty. This research contributes to the literature by clarifying the distinct roles of satisfaction and digital engagement strategies in shaping loyalty within higher education institutions.